Opportunities and threats for the theory and practice of speech therapy in the 21st century - Gunia, Grażyna (Selected issues from the theory and practice of speech therapy, 2018)
Intense socio-cultural, economic and technological changes cause changes in the theoretical and practical fields of many scientific disciplines. The aim of the study is to reflect on the opportunities and threats for diagnosis and speech therapy for people with speech and communication disorders. The subject of discussion is the discourse related to the strengths and weaknesses of the hitherto achievements of speech therapy, as a scientific discipline, profession and field of study in view of the challenges of the 21st century. Attention was also paid to the risks to speech therapy prevention associated with globalization and technological innovation.